Justification of Promising Areas for the Development of the Manufacturing Industry in Ukraine - Kyzym Mykola O.; Khaustova Viktoriia Ye.; Kramarev Hennadii V. (Problemi Ekonomiki, 2019)
The article deals with the analysis of the state of the manufacturing industry in Ukraine and justification of promising directions for its development. It is determined that one of the most important branches of the manufacturing industry is mechanical engineering, and the industries that have the potential for development in Ukraine are the manufacturing of civil aircraft and passenger cars. There analyzed the state of the civil aircraft manufacturing industry: the dynamic patterns of aircraft manufacturing in Ukraine, the capital equipment stock and its age composition, the country’s fleet of aircraft; there considered an integrated assessment of the competitiveness of domestic airplanes AN-148-100A and AN-140-100, the global aircraft exports, the structure of the global market for the final products and the global market for general aviation, the structure of the global market for aircraft engines, technical and economic indicators of national manufacturers of aircraft for general aviation and of most widely represented light Ukrainian-made airplanes. The comparative analysis of the aircraft manufacturing industry in Ukraine and individual countries is carried out. A strategic matrix of SWOT analysis of the aircraft manufacturing industry in Ukraine is developed. It is proved that the priority directions in the development of the domestic aircraft manufacturing industry are the production of small general-purpose airplanes as well as of aircraft components (aircraft engines, etc.). There analyzed the state of passenger car manufacturing: models of domestic-made passenger cars, the dynamic patterns of their production in the country, market segments in which Ukrainian automotive products are represented and the competitive environment, an integrated assessment of the technical level of domestic cars ZAZ Lanos T-150 and ZAZ Lanos T 100 in comparison to similar products from leading manufacturers in the C-Segment, positions of Ukraine and some European countries in the world ranking in terms of the number of passenger cars per 1,000 inhabitants, the dynamic patterns of the global passenger car manufacturing, the top 10 countries – car manufacturers / the largest passenger car exporters / the largest passenger car manufactures / global manufacturers of automotive components / countries leading in terms of sales of electric cars. A strategic matrix of SWOT analysis of the automotive industry in Ukraine in terms of passenger car manufacturing is built. It is justified that promising areas in the development of the domestic automotive industry in the context of passenger car manufacturing are the component assembly of electric vehicles in chain order: SKD (semi knock down assembly) ? MKD (medium knock down assembly) and production of components for passenger cars of global leading manufacturing companies.